Choral Singing in Prisons: Evidence-Based Activities to Support Returning Citizens - Cohen, Mary L. (The prison journal, 2019)
Choral singing in prisons can help incarcerated individuals identify as returning citizens instead of felons. Shadd Maruna argues that while many legal and penal rituals exist to convince individuals to identify as “offenders,” few such rituals are in place to reconnect formerly incarcerated people to identify as community members outside of prisons. Maruna describes successful reintegration rituals as symbolic and emotive, repetitive, community-based, and infused with a dynamic of challenge and achievement; they give form to political and social processes that enable successful reentry. I maintain that choral singing models positive reintegration rituals that promote prosocial connections between returning citizens and the societies to which they are restored.